2012
DOI: 10.1099/mic.0.063073-0
|View full text |Cite
|
Sign up to set email alerts
|

Population subdivision and the detection of recombination in non-typable Haemophilus influenzae

Abstract: The disparity in diversity between unencapsulated (non-typable; NT) and encapsulated, serotypable Haemophilus influenzae (Hi) has been recognized for some time. It has previously been suggested that the wider diversity evidenced within NTHi compared with typable lineages may be due to different rates of recombination within the encapsulated and NT populations. To examine whether there is evidence for different levels of recombination within typable and NT lineages of Hi, we performed a statistical genetic anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
(43 reference statements)
5
11
0
Order By: Relevance
“…The clusters obtained by Bayesian analysis correlate well with the classical subdivisions of the H. influenzae population but show limited concordance with the clades of Erwin et al (70). Compared with encapsulated isolates, a significantly larger proportion of unencapsulated isolates showed evidence of recombination, and when admixture was present, the total amount of recombination per strain was greater for unencapsulated strains (67 barrier to transformation, and factors other than the capsule may constitute decisive determinants of the recombination rate in the H. influenzae population.…”
Section: The Haemophilus Influenzae Groupsupporting
confidence: 55%
See 1 more Smart Citation
“…The clusters obtained by Bayesian analysis correlate well with the classical subdivisions of the H. influenzae population but show limited concordance with the clades of Erwin et al (70). Compared with encapsulated isolates, a significantly larger proportion of unencapsulated isolates showed evidence of recombination, and when admixture was present, the total amount of recombination per strain was greater for unencapsulated strains (67 barrier to transformation, and factors other than the capsule may constitute decisive determinants of the recombination rate in the H. influenzae population.…”
Section: The Haemophilus Influenzae Groupsupporting
confidence: 55%
“…Clade 2 corresponds closely to phylogenetic group II, and the major modifications are the dissection of phylogenetic group I into the remaining 12 clades and STs outside clades. Most recently, a statistical (Bayesian) genetic analysis of 819 distinct H. influenzae MLST genotypes was performed (67). The clusters obtained by Bayesian analysis correlate well with the classical subdivisions of the H. influenzae population but show limited concordance with the clades of Erwin et al (70).…”
Section: The Haemophilus Influenzae Groupmentioning
confidence: 99%
“…We have shown the existence of a discrete lineage structure that is stable over time and which did not measurably shift in response to PCV13. The clonality of the population was concordant with previous examinations of population structure based on MLST 21 and whole genomes of geographically diverse isolates collections 17 . The hierarchical analysis we used gave greater phylogenetic clarity and revealed hitherto unrecognized resolution of the lineages of NTHi.…”
Section: Discussionsupporting
confidence: 87%
“…Hence, phylogenetic tools, such as BEAST (Drummond and Rambaut 2007), need to be complemented with population genetic analysis that allows for an admixture within and between lineages. We have recently successfully identified significant variation in the extent of recombination and its association with several ecological and genetic factors using the population genetic software package, BAPS (Corander and Marttinen 2006; Corander and Tang 2007; Corander et al 2008a; Corander et al 2008b; Tang et al 2009; Cheng et al 2011), on large collections of DNA sequence data from pathogen populations (Hanage et al 2009; Castillo-Ramírez et al 2012; Connor et al 2012; Corander et al 2012; Willems et al 2012). For instance, we have showed that hospital-adapted virulent and resistant strains of the major source of nosocomial infections, Enterococcus faecium , display a marked reduction in their amount of recombination compared with commensal strains.…”
Section: Introductionmentioning
confidence: 99%